A study of female tennis players: Speedcourt training is effective on improving agility and change-of-direction - Zhihui Zhou; Jiawei Wang; Hao Wang; Guo Ru; Fanhui Kong (PeerJ)
Objective The aim of the present paper was to determine the impact of Speedcourt training on agility and change-of-direction (COD) in female tennis players, and to research the relevance between agility and lower limbs unilateral explosive power (UEP). Despite extensive research on agility training, limited studies have explored these effects specifically in female athletes and the number of exercises such as Speedcourt is also small, necessitating this investigation. Method Twenty-two female tennis players underwent SpeedCourt training for 6 weeks, respectively executed random sequence shuttle run training (RS group, N = 11, age: 22.36 ±  1.21 years) and fixed sequence shuttle run training (FS group, N = 11, age: 22.27 ± 1.27 years). The spider run, T-drill, reactive agility (RA) and triple crossover hop (TCH) before and after intervention were measured. And the TCH tested the left and right legs separately to detect the subject’s UEP. Results The two-way repeated measures analysis of variance showed significant improvements in spider run (p < 0.001, partial η2 = 0.95), T-drill (p < 0.001, partial η2 = 0.94) and RA (p < 0.001, partial η2 = 0.96). The RS group demonstrated significantly greater improvements in RA compared to the FS group, with statistical significance (p < 0.05, partial η2 = 0.184). And agility related tests showed moderate to strong correlations with unilateral explosive power. Conclusion Six-week Speedcourt training can effectively enhance the agility and change-of-direction of female tennis players. Incorporating lower limb explosive exercises into agility-specific training may further enhance agility improvements in female tennis players.